2019
DOI: 10.1159/000494620
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Symptoms Contribute to Persistent Fatigue in Prostate Cancer

Abstract: Purpose: Cancer-related fatigue is one of the most debilitating side effects of cancer and cancer therapy. We aimed to investigate co-occurring symptoms associated with persistent fatigue in men receiving external beam radiation therapy (EBRT) for nonmetastatic prostate cancer. Methods: A sample of 47 men with prostate cancer scheduled to receive radiotherapy (RT) were followed at baseline and 1 year after RT. Clinical and demographic data were obtained from chart review. Symptom measurements included urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…We previously showed that CRF during RT and one‐year post‐RT are dissociable in regard to comorbid symptoms and underlying mechanisms . Future studies will focus on discerning the cognitive and physical contributions of different fatigue subtypes.…”
Section: Discussionmentioning
confidence: 96%
“…We previously showed that CRF during RT and one‐year post‐RT are dissociable in regard to comorbid symptoms and underlying mechanisms . Future studies will focus on discerning the cognitive and physical contributions of different fatigue subtypes.…”
Section: Discussionmentioning
confidence: 96%
“…We are actively recruiting patients with various types of cancer to test this hypothesis. Secondly, previous studies have shown that cancer and cancer treatment may lead to fatigue via different mechanisms 39 , 49 , 50 . We only included participants that had confirmed cancer diagnoses before the start of treatment in order to focus on fatigue related to cancer itself instead of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were of fair[ 8 , 10 , 21 - 26 ] or high[ 7 , 11 - 13 , 27 , 28 ] quality. Only three of these studies had an adequate sample size[ 13 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rather, they found a subset of patients in their cohort who continued to experience fatigue for a year after RT, long after the treatment-associated hematologic toxicities had resolved. These findings suggest that acute and persistent fatigue may be independent phenomena that are mechanistically different; each may be driven by distinct underlying pathogenic processes[ 8 ]. Storey et al [ 13 ] suggested that the presence of post-treatment CRF may be more influenced by the patient’s current medical and psychological comorbidities than by the initial type of treatment received.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation